2021
DOI: 10.3390/nu13124271
|View full text |Cite
|
Sign up to set email alerts
|

Cameroonian Spice Extracts Modulate Molecular Mechanisms Relevant to Cardiometabolic Diseases in SW 872 Human Liposarcoma Cells

Abstract: The molecular pathophysiology of cardiometabolic diseases is known to be influenced by dysfunctional ectopic adipose tissue. In addition to lifestyle improvements, these conditions may be managed by novel nutraceutical products. This study evaluatedthe effects of 11 Cameroonian medicinal spice extracts on triglyceride accumulation, glucose uptake, reactive oxygen species (ROS) production and interleukin secretion in SW 872 human adipocytes after differentiation with 100 µM oleic acid. Triglyceride content was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, we clearly showed that on hepatic and adipose human cell models, those spice extracts inhibited ROS production and improved glucose uptake, reduced lipid storage, and exhibited antiinflammatory activity. 8,10 Our first chemical profiling suggested that polyphenols could potentially justify the biological properties observed. 7 The present study evaluated the Xylopia parviflora (A.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, we clearly showed that on hepatic and adipose human cell models, those spice extracts inhibited ROS production and improved glucose uptake, reduced lipid storage, and exhibited antiinflammatory activity. 8,10 Our first chemical profiling suggested that polyphenols could potentially justify the biological properties observed. 7 The present study evaluated the Xylopia parviflora (A.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, Adansonia digitata leaf extracts were found to reduce hyperglycaemia and hyperlipidaemia (including LDL-C reduction) of diabetic rats (117). A series of spice extracts from Cameroon has also been extensively studied in different experimental settings, showing that some of them may positively modulate enzymes relevant to arbohydrate/lipid metabolism and cardiometabolic disorders (118), oxidative stress, inflammation and metabolic pathways related to lipid biosynthesis in hepatic and adipose human cell models (119,120) and in animal models of diet-induced obesity (121). Taken together, well-characterized extracts from plants used in African traditional medicine have been shown to positively modulate molecular pathways associated with hypercholesterolaemia and other events promoting atherosclerosis, suggesting their use in cardiometabolic conditions of moderate severity.…”
Section: Ethnic Medicine and Cardiometabolic Disease: Experimental Ev...mentioning
confidence: 99%
“…Chiov., and Aframomum citratum (C.Pereira) K.Schum were chosen for gastro-protective evaluation. Our early studies showed that hydro-ethanolic extracts from these plants exerted antioxidant, hepato-protective, and enzyme inhibition activities [ 14 , 15 , 16 , 17 ]. In addition to their anti-inflammatory effects, the combination of these dietary plants, suggested by traditional Cameroonian medicine, might provide phytochemicals (mainly polyphenols) with synergistic gastro-protective effects.…”
Section: Introductionmentioning
confidence: 99%